Pengujian Aplikasi Inventory Manajemen System Berbasis Web Menggunakan Standar ISO/IEC 29119 (Studi Kasus :stemword/php-inventory-manajemen-system) - Irpan Sadath Komala Putra; Ahmad Zulfikar Setiawan; Chairul Anwar (Journal of Information Systems and Business Technology, 2025)
Software testing is a vital step in the information system development process, ensuring that the developed system has adequate quality, reliability, and security before being used in a real environment. Inventory information systems are one of the most important systems because they are directly related to the management of inventory data and business activities. The purpose of this study is to apply the ISO/IEC 29119 standard in testing the php-inventory-management-system application originating from the GitHub repository. Testing was carried out in a structured manner through the steps of test planning, test design, test execution, defect recording, and evaluation in accordance with the ISO/IEC 29119 guidelines. The testing methods used were black-box testing and static code analysis of the application's main modules. A total of 25 test cases were tested, with the results where 10 test cases were successful and 15 test cases failed. In addition, 10 defects were identified, which included defects related to security, input validation, and business logic, including critical defects that could pose security risks and inventory data inconsistencies. The evaluation results indicate that this application does not meet the software quality characteristics of ISO/IEC 25010, particularly in terms of security, reliability, and functional suitability. Therefore, the application is considered not yet ready for operational use and requires further improvement.